Promoting endurance training adaptations with nutritional interventions: The potential benefits of "low carbohydrate" training - Drust, B.; Morton, J. (Kinesiology, 2009)
Skeletal muscle responds to endurance exercise via increased transcription of metabolic and stress-related genes ultimately to yield increased steady-state levels of specific proteins. These changes in transcriptional activity are highly dependent on the mode, duration, intensity and frequency of the contractile stimulus. One of the major challenges for exercise physiologists over the coming decades is to identify the exercise `signal(s)` that are responsible for initiating the adaptive response and the precise signal transduction pathways which mediate the adaptive processes. In this regard, it is now becoming apparent that cellular energy status may have an important role to play in this process. For example, many stress-and metabolic-related genes are enhanced when the exercise is commenced under reduced pre-exercise muscle glycogen levels and attenuated when glucose is ingested during exercise. Taken together, such findings suggest that training under conditions of reduced carbohydrate availability from both endogenous and exogenous sources may provide an enhanced stimulus for inducing beneficial adaptations of skeletal muscle. This hypothesis is in marked contrast to the widely held belief that intense training periods should be supported by a high carbohydrate diet in order to maintain training intensity and replenish energy stores for future training sessions. This paper will outline the current thinking regarding the potential for carbohydrate availability to modulate the adaptations typically observed following periods of endurance training. Relevant data from the literature and our own laboratory is presented with a view to providing some potential advantages and disadvantages of training with reduced carbohydrate availability for both athletes and coaches.